MEDICAL TERMS IN PROFESSIONAL SPEECH OF FUTURE DOCTORS (Literature review) - Uktam D. Esanov; Abdunazar Kh.Jurayev; Madina Boboyeva (Central Asian Journal of Medicine, 2023)
Medical terms denoting human diseases are formed according to the same word-formation model: a root morpheme of different origin adding the suffix -it-, which is directly used in medical terminology to indicate the inflammatory nature of the disease: bronchitis, sinusitis, gastritis, etc.